(untitled) (Mustansiria Dental Journal, 2018)
Periodontitis is a persistent bacterial infection causing chronic inflammation in periodontal tissues. Type 2 diabetes mellitus (DM) is a common metabolic disease that is associated with increased prevalence and severity of periodontitis. Our aim is to evaluate periodontal treatment needs of type 2 diabetic Iraqi patients according to the age and the duration of DM. One hundred and seventy one type 2 diabetic Iraqi patients were enrolled in this study. Recording of gender, age, and duration of DM was done. Periodontal examination to evaluate treatment needs (TN) was performed by using community periodontal index of treatment needs (CPITN), Scoring for each patient was done by dividing his mouth into six sextants. CPITN showed a variation in the distribution of the patients according to age. In the age category (30-39) years; code 0 and code 1 represented 23.6 % and 59.8 % of the sextants respectively. Concerning treatment needs, only 11.8 % of patients did not need any treatment (TN 0). In the age category (40-49) years; code 1 was the most frequent code and represented 61.5% of the sextants . All patients in this age category need a sort of treatment . In the age categories (50-59) years and (60-69) years; code 3 represented 21.8% and 30.6% of the sextants respectively and TN3 represented 50% and 49.2% of the patients respectively. In this study, when the duration of DM is 1-5 years, code 3 represented only 13.6% of the sextants and periodontal treatment needs TN3 was 26.3% of patients while code 3 reached 26% of the sextants and TN3 represented 52.7% of the patients when the duration of DM was > 5 years. In conclusion periodontal treatment needs of type 2 diabetic patients became more complicated if the patients were older and the duration of DM was longer.